Bioinformatic analysis reveals pancreatic cancer molecular subtypes specific to the tumor and the microenvironment. (2nd July 2016) - Le Large, Tessa Y.S.; Mato Prado, Mireia; Krell, Jonathan; Bijlsma, Maarten F.; Meijer, Laura L.; Kazemier, Geert; Frampton, Adam E.; Giovannetti, Elisa
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease characterized by a dense desmoplastic reaction surrounding malignant epithelial cells. Interaction between the epithelial and stromal compartments is suggested to enhance its aggressive nature. Indeed, therapies targeting the stroma, as well as the tumor cells, may improve survival outcomes for patients. The evaluated study by Moffitt et al . used bioinformatic techniques to separate gene expression patterns of normal tissues from PDAC and stroma in a large cohort of samples. The researchers identified two different subtypes of PDAC ('classical' and 'basal-like') and surrounding stroma ('normal' and 'activated'). The basal-like subtype was associated with worse prognosis and a trend towards better response to adjuvant therapy. Hopefully, the molecular stratification of PDAC will potentially allow more personalized treatment strategies and guide clinical decision making.